Elections matter ten federal elections that shaped Australia - Jones, Benjamin T.; Bongiorno, Frank 1969-; Uhr, John 1951- (Monash University Publishing, 2018)
In a world of fake news and populist politics, elections can seem like theatre. With growing rates of informal votes and a perceived narrowing of differences between the major parties, do Australian elections really matter? Taking ten examples, this book argues that elections do matter (even when you think they don’t). It is not just elections with memorable jingles or triumphant campaigns from opposition to government that can shape the nation. Could it be that the Labor loss in 1969 formed the country more than the famous win in 1972? Or did the return of the Coalition in 1954 have more impact than securing government in 1949? Elections Matter looks at prime ministers and policies that never were and examines how the democratic process could have produced a different country. Had key elections taken a different turn, Australia might have had a different constitution, a different head of state, a different health and education system and a different foreign policy approach. This book looks at ten elections that formed Australia